HAK IJBAR WALI DALAM PERKAWINAN WANITA HAMIL DI LUAR NIKAH DENGAN SELAIN LAKI-LAKI YANG MENGHAMILI PERSPEKTIF MAZHAB HANAFI - Fadilah, Umi Nuril; Umami, Hafidhul (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2024)
Promiscuity often leads to premarital pregnancy. Then the pregnancy became one of the reasons for parents to quickly marry off their daughter, either to the man who got her pregnant or to another man, with the aim of covering up the family's disgrace. The problem is when a girl is already pregnant while dating, but a guardian does not approve of her daughter marrying a man who has impregnated her daughter. The guardian wants to marry his daughter to another man who is considered better than the man who impregnated his daughter. According to the Hanafi school of law, guardianship of women who are pregnant out of wedlock or because of adultery is only sunnah. So he is no longer the authority or authority of the mujbir guardian. If her guardian wants to marry her, he must have her consent first. As for the form of consent to marry a woman who is pregnant out of wedlock or because of adultery, according to the Hanafi school, it is equated with that of a virgin, namely simply by remaining silent.